Glucagon dynamics during hypoglycaemia and food‐re‐challenge following treatment with vildagliptin in insulin‐treated patients with type 2 diabetes. Issue 9 (17th March 2014) - Farngren, J.; Persson, M.; Schweizer, A.; Foley, J. E.; Ahrén, B.
Abstract Aims To determine the effects of dipeptidyl peptidase‐4 (DPP‐4) inhibition on glucagon dynamics in patients with insulin‐treated type 2 diabetes (T2D). Methods The study was a single‐centre, double‐blind, randomized, placebo controlled crossover study in patients with T2D, mean age 59 ± 6 (s.d.) years and mean haemoglobin A1c 7.7 ± 0.8%, treated with exogenous insulin with or without oral antihyperglycaemic agents. Patients received vildagliptin (50 mg BID) or placebo as add‐on to insulin for 4 weeks in random order with a 4‐week washout in‐between. On day 28 of the respective treatment, patients were served a standard meal (500 kcal) followed by a hyperinsulinaemic hypoglycaemic clamp (target 2.5 mmol/l) and a subsequent food re‐challenge (700 kcal). The completers population (n = 29) was analysed. Results Glucose levels were lower with vildagliptin than with placebo during the meal [areas under the curve (AUC) 1.23 ± 0.07 vs. 1.46 ± 0.05 mol/l min, P < 0.001] and similar between the groups during the clamp. During the meal, glucagon levels were lower with vildagliptin (AUC 1.98 ± 0.15 vs. 2.15 ± 0.17 nmol/l min, P = 0.016). In contrast, the glucagon counter‐regulation to the insulin‐induced hypoglycaemia was sustained by vildagliptin (6.05 ± 1.20 pmol/l during vildagliptin vs.6.94 ± 1.09 pmol/l during placebo, NS). During the food re‐challenge after hypoglycaemia, glucagon levels were, again, significantly lower after vildagliptin (AUC 1.30 ± 0.11 vs. 1.52 ± 0.12 nmol/l min, P < 0.039). Glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) levels were significantly elevated by vildagliptin compared to placebo during meal, hypoglycaemia and food re‐challenge. Conclusions Vildagliptin action to block GLP‐1 and GIP inactivation by DPP‐4 improves glucagon dynamics during hypoglycaemia, hyperglycaemia and food re‐challenge.